2017
DOI: 10.1111/cei.12971
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome gene profile is modulated in septic patients, with a greater magnitude in non-survivors

Abstract: Inflammasome signalling induces the processing and secretion of interleukin (IL)-1β and IL-18 which, coupled with pyroptosis, activate further the inflammatory response. In the present study we evaluated the expression of genes involved in inflammasome signalling pathways in septic patients, their interaction networks and the predicted functions modulated in survivors and non-survivors. Twenty-seven patients with sepsis secondary to community-acquired pneumonia admitted to intensive care units from three gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
2
42
2
1
Order By: Relevance
“…Pyroptosis is an inflammatory form of programmed cell death. In general, pyroptosis protects multicellular host organisms against invasive pathogenic bacteria and microbial infections; however, it also causes sepsis and septic shock when overactivated ( Figure 1 ) [ 15 , 21 23 ]. In the 20th century, the discovery of Toll-like receptor- (TLR-) 4 was a key landmark for understanding innate- and specific-immune responses in infectious diseases, especially in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis is an inflammatory form of programmed cell death. In general, pyroptosis protects multicellular host organisms against invasive pathogenic bacteria and microbial infections; however, it also causes sepsis and septic shock when overactivated ( Figure 1 ) [ 15 , 21 23 ]. In the 20th century, the discovery of Toll-like receptor- (TLR-) 4 was a key landmark for understanding innate- and specific-immune responses in infectious diseases, especially in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found in macrophages and neutrophil granulocytes and can recognize pathogens like bacteria. The inflammasome inter alia consists of NLR family pyrin domain containing 3 (NLRP3) which is up-regulated in sepsis [ 26 ]. Activation of NLRP3 inflammasome causes interleukin 1 beta (IL-1β) release.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipase ( PLC ) proteins are mainly responsible for metabolizing inositol lipids and recent studies have shown that impairment of lipid metabolism is one of the major changes among patients with sepsis secondary to hospital-acquired pneumonia (49) . Finally, the NLR Family Pyrin Domain Containing 1 ( NLRP1 ) gene, which is one of the many genes responsible for the activation of the NLR-inflammasome cascades was found to be significantly altered among septic patients in a recent study (50) .…”
Section: Discussionmentioning
confidence: 99%